2004
DOI: 10.1029/2004jc002422
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of a coastal current on a steep slope in presence of a cape: The case of the Promontorio di Portofino

Abstract: [1] A process study aimed at investigating the winter circulation in the area of the Promontorio of Portofino (northwestern Mediterranean) is presented, motivated by historical current measurements suggesting the presence of an attached recirculating eddy in the lee of the Promontorio (cape). A sensitivity study is first performed in an idealized setting, considering the interaction of a steady incoming current with the cape. Numerical experiments are performed using both two-dimensional (2-D) (vertically inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 53 publications
3
44
0
Order By: Relevance
“…The upwelling jet deflection and corresponding cyclonic circulation due to the presence of a cape and the intensified upwelling in the leeside of the cape is consistent with several studies (Barth et al, 2000;Gan and Allen, 2002;Doglioli et al, 2004;Kuebel Cervantes and Allen, 2006;Meunier et al, 2010;Perlin et al, 2011;Liu and Gan, 2014). However, most of these studies deal with steady upwelling regimes or with relaxation periods of more than one day, and do not describe the diurnal variability caused by a daily oscillating upwelling regime.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…The upwelling jet deflection and corresponding cyclonic circulation due to the presence of a cape and the intensified upwelling in the leeside of the cape is consistent with several studies (Barth et al, 2000;Gan and Allen, 2002;Doglioli et al, 2004;Kuebel Cervantes and Allen, 2006;Meunier et al, 2010;Perlin et al, 2011;Liu and Gan, 2014). However, most of these studies deal with steady upwelling regimes or with relaxation periods of more than one day, and do not describe the diurnal variability caused by a daily oscillating upwelling regime.…”
Section: Discussionsupporting
confidence: 52%
“…Ganju et al (2011) pointed out the importance of topographic features in the circulation over the inner-shelf by showing that the dynamical balance was dominated by pressure gradient and horizontal advection terms, which varied with subtle bathymetric changes. Finally, several studies found that non-linear advection is particularly important in the vicinity of topographic features (Doglioli et al, 2004;Meunier et al, 2010;Liu and Gan, 2014). It is expected that Cape Sines will have a similar effect on the circulation, which will promote the generation of localized wind-forced pressure gradients and enhance the cross-shelf exchange in the leeside of the cape.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Downstream of the cape, the current widens, following the shelf. A small recirculation region can be seen in the lee of the cape, with reduced sampling suggestive of a "shadow zone" resulting from the classical detachment of a boundary current in the presence of an obstacle (Doglioli et al 2004). The WAC appears connected with the interior flow through two branches of the cross-basin recirculations, along the slopes of the MAP and SAP, respectively.…”
Section: The Dart Area Of Interest and The Methodologymentioning
confidence: 97%
“…The general circulation within the Ligurian-Provençal basin follows a cyclonic gyre, being a part of the general cyclonic circulation of the Western Mediterranean Sea, due to the presence of baric depressions which produce an intensification of the coastal currents towards the west. The gyre shows a seasonal cycle; its extension and intensity are related to the seasonal variations of the atmospheric forcing (Esposito and Manzella, 1982;Dagnino, 1978;Doglioli et al, 2004;Manzella, 1983). This hydrodynamic feature involves the two main Mediterranean water masses, i.e.…”
Section: Physical Oceanography Of the Ligurian Seamentioning
confidence: 99%